2013
DOI: 10.1371/journal.pone.0057979
|View full text |Cite
|
Sign up to set email alerts
|

Altered Processing of Amyloid Precursor Protein in Cells Undergoing Apoptosis

Abstract: Altered proteolysis of amyloid precursor protein is an important determinant of pathology development in Alzheimer's disease. Here, we describe the detection of two novel fragments of amyloid precursor protein in H4 neuroglioma cells undergoing apoptosis. Immunoreactivity of these 25–35 kDa fragments to two different amyloid precursor protein antibodies suggests that they contain the amyloid-β region and an epitope near the C-terminus of amyloid precursor protein. Generation of these fragments is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Our studies have shown that inhibition of ADAM10, which is established as the -secretase that constitutively cleaves APP, interferes with APP proteolysis [ 19 ]. APP is a transmembrane protein, which is cleaved by α, β and γ-seceretases to generate fragments with variable cellular functions [ 55 - 57 ]. Since fendiline seems to inhibit ADAM10, and because APP is known to play a role in PDAC cell proliferation [ 19 ], we examined if cells treated with fendiline show alterations in APP.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies have shown that inhibition of ADAM10, which is established as the -secretase that constitutively cleaves APP, interferes with APP proteolysis [ 19 ]. APP is a transmembrane protein, which is cleaved by α, β and γ-seceretases to generate fragments with variable cellular functions [ 55 - 57 ]. Since fendiline seems to inhibit ADAM10, and because APP is known to play a role in PDAC cell proliferation [ 19 ], we examined if cells treated with fendiline show alterations in APP.…”
Section: Resultsmentioning
confidence: 99%
“…APP and its proteolytic products are implicated in both normal nervous system function and Alzheimer's disease pathogenesis (Selkoe and Hardy, 2016). APP processing and Aβ peptide production are promoted by factors including NMDAR activation (Bordji et al, 2010;Hoey et al, 2009), JNK activation (Mazzitelli et al, 2011;Triaca et al, 2016), and cell death (Fiorelli et al, 2013), which are all biochemical and cerebral features of Ddo −/− aged brain. Interestingly, we observed increased age-dependent cortical immunostaining of APP in neuron cell soma of these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Although Annexin is indeed for apoptosis, PI also marks apoptotic cells [29] . This is evident in our present results in Figs.…”
Section: Discussionmentioning
confidence: 99%